Primary Hyperparathyroidism during Pregnancy: Two Tales with Different Outcomes - Loh, Yoon Doong; Mohd Ali, Masliza Hanuni (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Primary hyperparathyroidism (PHPT) is rare in pregnancy. This condition is challenging to diagnose and manage due to the limited diagnostic and therapeutic options that are safe during pregnancy. If not diagnosed and managed in a timely manner, serious maternal and foetal complications may occur. We report two cases, one with surgical intervention and one without, to show the importance of timely surgical intervention and discuss the challenges in the management of PHPT in pregnancy.